2017
DOI: 10.1002/bdr2.1095
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Medication Use and Birth Defects in the National Birth Defects Prevention Study

Abstract: While new associations were identified, our findings are relatively consistent with previous NBDPS analyses. Our findings suggest thyroid medication use is not associated with most birth defects studied in the NBDPS, but may be associated with some specific birth defects. These results should not be interpreted to suggest that medications used to treat thyroid disease are teratogens, as the observed associations may reflect effects of the underlying thyroid disease. Birth Defects Research 109:1471-1481, 2017.©… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…Cardiac (situs inversus ± dextrocardia and cardio outflow tract defects) and renal (isolated unilateral kidney a/dysgenesis) anomalies were found in one study but with five or fewer cases for each anomaly (Clementi et al, 2010). Cardiac (coarctation of the aorta and aortic valve stenosis) were found in a different study but with four or fewer cases for each anomaly (Howley et al, 2017). PTU alone was associated with anomalies of the face and neck (Andersen et al, 2013;Andersen, Olsen, Wu, & Laurberg, 2014), ear (Andersen et al, 2017), urinary systems (Andersen et al, 2014;Andersen et al, 2017;Korelitz et al, 2013), and musculoskeletal systems (Seo, Kim, & Chung, 2018) using retrospective searches based on ICD codes.…”
Section: Propylthioruacilmentioning
confidence: 95%
See 2 more Smart Citations
“…Cardiac (situs inversus ± dextrocardia and cardio outflow tract defects) and renal (isolated unilateral kidney a/dysgenesis) anomalies were found in one study but with five or fewer cases for each anomaly (Clementi et al, 2010). Cardiac (coarctation of the aorta and aortic valve stenosis) were found in a different study but with four or fewer cases for each anomaly (Howley et al, 2017). PTU alone was associated with anomalies of the face and neck (Andersen et al, 2013;Andersen, Olsen, Wu, & Laurberg, 2014), ear (Andersen et al, 2017), urinary systems (Andersen et al, 2014;Andersen et al, 2017;Korelitz et al, 2013), and musculoskeletal systems (Seo, Kim, & Chung, 2018) using retrospective searches based on ICD codes.…”
Section: Propylthioruacilmentioning
confidence: 95%
“…PTU is associated with an increase in congenital anomalies less often than MMI/CMZ but some studies have noted an increased risk (Andersen, Lonn, Vestergaard, & Torring, 2017;Andersen, Olsen, Wu, & Laurberg, 2013;Howley et al, 2017;Leung, Yamamoto, Luca, Beaudry, & McKeen, 2015). A case study identified intestinal malrotation with congenital bands (Leung et al, 2015).…”
Section: Propylthioruacilmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the comorbidities that pose a teratogenic risk include gestational diabetes mellitus which is associated with higher risk of congenital malformation,[ 6 7 8 ] thyroid related diseases and medications[ 9 10 ] and epilepsy medications. [ 11 12 13 ] Awareness of women showed insufficient knowledge regarding the teratogenicity of gestational diabetes mellitus,[ 14 ] thyroid diseases and medications[ 15 ] and epileptic medications.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid disorders are prevalent conditions in women of reproductive age14 and may affect female fertility in various ways, including anovulatory cycles, luteal phase defect, high prolactin levels, and sex hormone imbalances,57 which may cause both infertility and adverse pregnancy outcomes 812. Assisted reproductive technology (ART) treatment is a relevant intervention in women who cannot conceive naturally, and recent studies have shown that women with ulcerative colitis, Crohn’s disease, and rheumatoid arthritis have a decreased chance of giving birth to a live-born child after ART treatment compared to other women undergoing ART treatment 1315.…”
Section: Introductionmentioning
confidence: 99%